Corduroy - Freeman, Don, 1908-1978. (New York : Puffin, 1976)
A teddy bear spends his days waiting in a store for someone to buy him.
"First published by The Viking Press, 1968"--T.p. verso.
Book Links (A.L.A.).
School Library Journal.
Wilson's Children.
3.2.
3.2
Keywords: Corduroy (Fictitious character) -- Fiction; Teddy bears -- Fiction; Toys -- Fiction; Corduroy (Fictional character) -- Fiction; Teddy bears -- Fiction; Toys -- Fiction